Recobrimento, condicionamento, secagem e armazenamento de sementes de melancia - Nunes, Tenessee Andrade (2011)
With the objective of evaluate the performance of seed of two cultivars of watermelon (Charleston Gray and Crimson Sweet) conducted an experiment in the Laboratory of Seeds Analysis of Universidade Federal Rural do Semi-árido (UFERSA) during the months of December 2009 to June 2010. Was used four seed lots of two watermelon cultivars Charleston Gray and Crimson Sweet. For the phosphorus coating the seeds were agitated inside a plastic bag near the source of phosphorus used in their respective dose, so that they adhere to the seeds. After the application of phosphorus sources for seeds proceeded to the coating at a dose of 0,8 ml / 100 g of seeds with a syringe using the polymer ColorSeed HE Rigrantec ® red for the cultivar Charleston Gray and blue for the cultivar Crimson Sweet. The sources of phosphorus and phytin were bicalcium phosphate. Immediately after drying the polymer, we proceeded to test for evaluation of existing and development of plants and the influence of phosphorus source and dosage in these cultivars of watermelon. The variables analyzed were: germination, first count germination (CP), accelerated aging (EA), plus the weight of thousand seeds and uniformity test for standardization of the lots and the variables of seedling growth, seedling emergence and emergence speed index. The experimental design was completely randomized and averages of quantitative data (doses) were adjusted by regression testing. The germination of the cultivar Crimson Sweet watermelon after the accelerated aging test showed that the seeds subjected to coating with the bicalcium phosphate showed higher values when compared to coated seeds phytin. Data from the first count in this experiment suggest that higher concentrations of P in seeds, exogenously, will provide greater availability of energy for metabolic activities of the seed, which would lead to greater initial seedling growth and development of the largest and fastest root system, resulting in increased absorption of nutrients and, consequently, the productive capacity of the plant.